Rat natural killer cell antigen, NKR-P1, related to C-type animal lectins is a carbohydrate-binding protein - Bezouska, K; Vlahas, G; Horváth, O; Jinochová, G; Fiserová, A; Giorda, R; Chambers, W H; Feizi, T; Pospísil, M (The Journal of biological chemistry, 1994)
Natural killer receptor protein 1 (NKR-P1, a family of proteins), which is a dimeric transmembrane protein predominantly on rat and murine natural killer cells, contains an extracellular motif related to calcium-dependent animal lectins. The domain architecture of this protein and the finding that its cross-linking with antibody results in activation of natural killer cells make it a promising candidate for a receptor function. We have expressed a full-length NKR-P1 protein of the rat in COS cells and prepared soluble extracellular fragments by controlled proteolysis or by expression of truncated cDNA in bacteria. Dimerization of soluble NKR-P1 is predominantly dependent on the presence of an intact juxta-membrane stalk region and independent of N-glycosylation. Binding and inhibition studies using monosaccharides and neoglycoconjugates indicate that NKR-P1 is a lectin with a preference order of GalNAc > GlcNAc >> Fuc >> Gal > Man. At neutral pH, Ca2+ is tightly associated with the protein such that only a proportion can be removed by 10 mM EGTA. However, NKR-P1 can be decalcified completely at pH 10 with a total loss of carbohydrate binding. After recalcification at pH 8, carbohydrate binding is completely restored. Thus, NKR-P1 differs from other calcium-dependent animal lectins investigated so far in its pattern of monosaccharide recognition and in the tightness of Ca2+ binding.
Keywords: Calcium; lektiny typu C; Chlorocebus aethiops; gelová chromatografie; Macromolecular Substances; Substrate Specificity; Protein Binding; klonování DNA; ledviny; vápník; Antigens, Surface; Kidney; antigeny povrchové; lektiny; krysa rodu Rattus; Lectins, C-Type; Recombinant Proteins; makromolekulární látky; zvířata; buňky NK; membránové glykoproteiny; Killer Cells, Natural; Membrane Glycoproteins; buněčné linie; Cercopithecus aethiops; Monosaccharides; NK Cell Lectin-Like Receptor Subfamily B; rekombinantní proteiny; transfekce; Kinetics; Lectins; Cell Line; substrátová specifita; vazba proteinů; Rats; Transfection; monosacharidy; lektinové receptory NK-buněk - podrodina B; Animals; Cloning, Molecular; Chromatography, Gel; kinetika